The problem of transcription of the text in Khosrow and Shirin - Mamyrbek Г.М.; Seitbekova А.А. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
The article analyzes the problems of translating the text of the written heritage, marked with Arabic script, into Cyrillic, and also talks about the principles of transcription and transliteration. The author of the article analyzed the fact that during the Soviet period, when translating the written heritage preserved in the Arabic script into Cyrillic, a tradition of transcription was formed, close to the Uzbek or Tatar languages, and that this process continued after gaining independence, and suggested the need for transcription of the written heritage closer to the Kazakh language, and pointed out the main reasons for this. The article analyzes the positions of domestic and foreign scientists in the transcription of Arabic scriptures using examples. In particular, Turkologists E. Nadjip, V.Radlov, E. Sevortyan, V. Nadelyaev, D. Nasilov, E. Tenishev, A. Shcherbak, as well as Turkish scientists N. Hadjieminoglu and B. Dag analyze the positions and main features of the transcription of Arabic written in Cyrillic and Latin. The fact that Turkish scientists used symbols that are not in the Turkish alphabet when transcribing Khosrow and Shirin monument and the main reasons for this are shown in the article using specific examples. The article also highlights the similarities and differences between practical transcription and transliteration and analyzes the functions of both. Focusing on the history of the study of the concepts of transcription and transliteration in linguistics, comparative studies of the conclusions of scientists were carried out. The similarities and differences between the two concepts are analyzed.